DISCUTIENDO LOS PROGRAMAS DE PERMANENCIA ESTUDIANTIL EN LA EDUCACIÓN UNIVERSITARIA - de Lima, Maria Janete (Universidad de Panamá, Extensión Universitaria de Soná, 2023)
This article deals with Student Assistance Policies at the Public University, focusing on two Student Assistance programs: The University Residence and the Undergraduate Teaching Assistance Program (PAEG), of the CFP/UFCG. It aims to analyze student assistance programs as policies of neoliberal governmentality and the construction of qualified students' permanence in university education, considering the discourses of “assistance” and “permanence”. The theoretical bases bring Foucault's governmentality. The interview was used for data collection, from the perspective of qualitative research, and Foucault's discourse analysis was developed to treat the data. Regarding the mechanisms of access and permanence of students in the University Residence and PAEG programs at CFP, we can infer that there is legislation that the UFCG Institution, executed through the PRAC. Students present speeches with highlights for positive and negative aspects, as well as having a broad way of presenting a very personal and unilateral understanding of assistance policies.